The PanCam instrument for the ExoMars rover - Coates, A; Jaumann, R; Griffiths, A; Leff, C; Schmitz, N; Josset, J; Paar, G; Gunn, M; Hauber, E; Cousins, C; Cross, R; Grindrod, P; et al. (Mary Ann Liebert, 2017)
The scientific objectives of the ExoMars rover are designed to answer several key questions in the search for life on Mars. In particular, the unique subsurface drill will address some of these, such as the possible existence and stability of subsurface organics. PanCam will establish the surface geological and morphological context for the mission, working in collaboration with other context instruments. Here, we describe the PanCam scientific objectives in geology, atmospheric science, and 3-D vision. We discuss the design of PanCam, which includes a stereo pair of Wide Angle Cameras (WACs), each of which has an 11-position filter wheel and a High Resolution Camera (HRC) for high-resolution investigations of rock texture at a distance. The cameras and electronics are housed in an optical bench that provides the mechanical interface to the rover mast and a planetary protection barrier. The electronic interface is via the PanCam Interface Unit (PIU), and power conditioning is via a DC-DC converter. PanCam also includes a calibration target mounted on the rover deck for radiometric calibration, fiducial markers for geometric calibration, and a rover inspection mirror. Key Words: Mars-ExoMars-Instrumentation-Geology-Atmosphere-Exobiology-Context. Astrobiology 17, 511-541.